Analisis Faktor-Faktor Yang Mempengaruhi Minat Petani Terhadap Usaha Tani Nilam (Pogostemon Cablin) di Kelurahan Toriki Kecamatan Anggaberi Kabupaten Konawe - Pemi Pemi; Leni Saleh; I Made Sukratman (Mikroba : Jurnal Ilmu Tanaman, Sains Dan Teknologi Pertanian, 2024)
The purpose of this study was to analyze the factors that influence farmers' interest in cultivating patchouli in Toriki Village, Anggaberi District, Konawe Regency. The population in this study were all patchouli farmers in Toriki Village, totaling 15 farmers. So that the sample of this study was 15 people. The measurement scale used in this study was the Likert Rating Scale (SLR). To analyze the factors that influence farmers' interest, multiple regression analysis was used. The results showed that variables (X1), (X2), (X4) influenced the interest of patchouli farmers (Y). While variable (X3) showed a negative relationship but had a significant effect on the interest of patchouli farmers (Y) in Toriki Village. The t-test showed that all variables influenced farmers' interest in cultivating patchouli because they had a t count that was greater than the t table (X1 = 7.895, X2 = 3.556, X3 = -3.708, X4 = 10.347> t table 1.81246). from the results of the f test, it shows that the four variables (X1, X2, X3, X4) have a simultaneous effect on the dependent variable (Y) with a calculated f value of 45.345> f table 3.48. The determination coefficient test (R Square) shows an R Square value of 0.948, meaning that the independent variables can explain the dependent variable by 94.8%.